Evaluate Analysis and Decision-Making of Nurses Regarding Sepsis Assessment and Management in Critically Ill Patients - KHAN, IRUM; Ashfaq, Shazia; Khushid, Khadeeja (Biological and Clinical Sciences Research Journal, 2025)
Sepsis is a life-threatening condition that requires timely diagnosis and management to prevent organ failure and mortality in critically ill patients. Nurses play a pivotal role in early sepsis recognition and intervention, yet gaps in knowledge, attitudes, practices (KAP), and decision-making can compromise patient outcomes. Understanding these gaps is crucial for improving sepsis care in Intensive Care Units (ICUs) and Emergency Departments (EDs). Objective: To evaluate nurses’ knowledge, attitudes, and practices towards sepsis assessment and management in critically ill patients. Methodology: A cross-sectional study was conducted in the Intensive Care Unit of Nishtar Hospital from Aug 2024 to November 2024. A total of 100 ICU/CCU nurses and those working in the emergency department were selected by convenience sampling. A 32-item questionnaire collected data to assess knowledge, attitudes, and practices for sepsis. The 24-item nursing decision-making instrument was used to test the decision-making skills. Results: The mean knowledge score was 5.1 ± 1.8 with 83% of nurses with poor awareness. The mean attitude score was 2.0 ± 0.9 with 85% of nurses having negative attitudes. The mean practice score was 79 ± 17.8 with 72% possessing poor practice skills. Lastly, the mean decision-making score on NDMI was 63.3 ± 19.6. The qualification (p=0.010, p=0.009) and work experience (p=0.005, p=0.050) significantly influenced these scores. Knowledge and practice scores differ significantly concerning modes of decision-making (p<0.001, p=0.020).Conclusion: ICU and emergency department nurses had poor knowledge, attitudes, practices, and decision-making for the assessment and management of sepsis in ICU patients. Training protocols and policy changes are needed to improve nurses’ quality of care and efficiency.